The impact of an online hybrid reading intervention on the reading comprehension and strategy use of Iranian English for specific purposes students in relation to an evaluated researcher-made ESP textbook - Meysam Muhammadpour; Masoud Khalili Sabet (Springer, 2024)
Abstract Research suggests that English for Specific Purposes (ESP) students in English-as-a-Foreign-Language (EFL) contexts have difficulties understanding the passages in technical English textbooks of various fields of study including computer software engineering. Few experimental studies to date have investigated the effect of an online hybrid reading intervention on the reading comprehension performance of these students. To fill this gap, the present experimental study sought to assist these students with comprehending the passages of an ESP textbook entitled ''Technical English for Computer Software Engineers'', developed for computer software engineering students of a non-profit university in Babol, Iran. In doing so, an 8-session online hybrid reading intervention featuring cognitive and metacognitive strategies was administered to an experimental group (n = 30) of ESP students, while the control group (n = 30) followed the conventional approach to teaching the reading skill. To track the participants' reading comprehension, International English Language Testing System (IELTS) reading tests were used before and after the intervention. Results showed that the treatment led to a statistically significant difference between the two groups in terms of the reading comprehension and strategy use. In addition, the teachers' and students' perceptions with regard to the whole textbook were reported. Findings bear pedagogical significance for all the stakeholders.